Review of the cedar and oak forest-associated Epuraea latipes species group (Coleoptera: Nitidulidae, Epuraeinae), with description of a new species from southern Turkey - Avgın, Sakine; Magri, Donatella; Antonini, Gloria; Mancini, Emiliano; Jansson, Nicklas; Lasoń, Andrzej; Cline, Andrew; Audisio, Paolo (Entomologica Fennica, 2012)
A new species of Epuraea, Epuraea sutcuimamun Avgm, Lasoń & Audisio sp. n., from southern Turkey (Taurus Chain) was identified using morphological analyses. This species is a member ofa circum—Mediterranean endemic group of sap beetles, the Epuraea latipes species group of the Dadopora lineage, which are mostly associated with cedar (Cedrus spp.) forests. Herein, the new species is described, the previously unknown association of the little-known Epuraea subparallela Grouvelle 1896 with meso-xerophilous oaks is reported, and some new records from southern Turkey (Taurus Chain) are listed for the latter species (previously only known from the Nur Mts. in SE Turkey, Osmaniye and Iskenderun provinces). An identification key to species of Dadopora lineage is also provided. Finally, the main palaeogeographic events affecting the Miocene to Holocene dispersal and evolution of species/populations of the Dadopora lineage on cedars and oaks, and the coincident distributional dynamics of Western Palaearctic Cedrus populations throughout the Mediterranean Basin, are discussed.